A phase 2 trial of deep-inspiration breath hold in radiotherapy of gastric lymphomas - Peter Meidahl Petersen; Laura Ann Rechner; Lena Specht (Physics and Imaging in Radiation Oncology, 2022)
Background and purpose: Radiotherapy (RT) is an important part in the treatment of gastric lymphomas and the prognosis after radiotherapy is very good with a good chance of long-term survival, so prevention of long-term adverse effects is important. In patients with gastric lymphomas cardiac late effects are of most concern. The aim of this study was to assess if the dose to the heart could be reduced with deep inspiration breath-hold (DIBH) without compromising the dose to the target or increasing the risk of other late effects. Methods and patients: Fifteen patients with gastric lymphoma were included. RT plans were made using DIBH and Free breathing (FB) scans. Clinical target volume (CTV) was the stomach plus 1 cm margin. The heart and surrounding organs at risk (OAR) were contoured. Two sets of plan comparisons were made, one with 1 cm CTV to planning target volume (PTV) margin in both DIBH and FB and one set with an additional 5 mm CTV to PTV margin in cranio-caudal direction with FB. Datasets were analysed with Wilcoxon signed rank test for non-parametric paired data. Results: All patients tolerated the procedures and were treated with volumetric arc therapy technique in DIBH. Target coverage was kept equal between FB and DIBH, while a statistically significant reduction of the estimated does to the heart was seen with DIBH. Median mean heart dose was reduced from 7.1 Gy (5.7–12) to a median of 3.2 Gy (1.2–7.0) and heart V20 from a median of 54 (17–106) cm3 to 15. (0.0–78) cm3. The estimated mean doses to the liver, duodenum, pancreas and spinal cord were at the same level. Conclusion: This clinical trial of RT with DIBH for gastric lymphomas showed that the heart dose could be reduced without compromising PTV coverage. The doses to abdominal OARs were similar with FB and DIBH.